Pretoria Student Law Review 2019-13 (Pretoria University Law Press (PULP), 2019)
Honoured to be the first black Editor-in-Chief of the University of Pretoria's Law Review, an annual publication which is the pride of the best law faculty in Africa (according to the Times Higher Education World University Rankings), I proudly present to you the 2019 edition of the Pretoria Student Law Review (PSLR). As I reflect on how the 17 year old me decided to one day become the President of the Law Review of 'whichever' tertiary institution I found myself at, after having been inspired by the first black Harvard Law Review President, President Barack Obama, who was appointed as such a year before my birth, I stand amazed at how inspiration and vision are literally a foretaste of a future God would have predestined for one, in this case mine. With a vision to create a boldly outlined legacy for the PSLR, I spearheaded the setting up of systems that would last the lifespan of the PSLR, with my main focus as Editor-in-chief being on branding and operations. I am proud to announce that as the PSLR we now have our official email address; website; annual calendar; set dates for the publishing of our annual 'Call for Submissions' and annual 'Call for Applications' for the PSLR Editorial Board; official communication templates used for correspondence with our stakeholders namely, the Reviewers, the authors, the Editors and the public at large; sound disciplinary procedures and a significant social media presence. A consistent teammate in bringing this to fruition was Dr Gustav Muller, in his capacity as the PSLR Guardian. Building on last year's legacy, for the first time in its history, the PSLR used the same cover consecutively in different years, namely 2018 & 2019. It is at this juncture that I would like to acknowledge vi and thank my predecessor, Mr Jürgen Zwecker, for the legacy he created for the PSLR, specifically in terms of its image and the foundation he laid for its branding. A legacy I have only been too glad to build upon and continue. To our photography genius Adebayo Okeowo, thank you very much for your exceptional cover art. Our conference calls between New York and Pretoria, with an emphasis on the different time zones which we managed remarkably well, yielded fruit. Having thoroughly read each article and footnote in this edition, dotted every 'i' dotted and crossed every 't', I cannot help but marvel at the culture of robust debate, research and relentless fact-finding cementing and holding together the identity of the University of Pretoria's Law faculty. The sharp legal minds it has moulded, may they forever be emblematic of the excellence, critical thinking and fruits of pluralism, cultural integration and transformation, which not only define the faculty but which will further entrench its spot on the world map. This PSLR edition also brags of articles from sister institutions and other African countries, as has been the case with previous editions. It would be out of character for me not to acknowledge my exceptional team of Editors who committed to making this a quality publication, backing and forthing with the authors and reviewers. Thank you Thato Maruapula, Mzwandile Ngidi and Frieda Shifotoka! To the reviewers, your adjudication laid the foundation for this year's PSLR edition and we are grateful to you, especially for doing so gratuitously. To the authors, you have started your publishing career on a remarkable note. To Lizette Hermann and Elzet Hurter, your dedication to the PSLR for over a decade, has us as the Editorial Board and the Law Faculty forever indebted. To the renowned philosopher and theologian hailing from Georgetown University and New York University, who introduced me to publishing, my dear father Prof Jemison Kurasha, ndinotenda Mukanya (thank you Dad, father of the clan). To my exceptional mentor and late mother, the first female Pro-Vice Chancellor and Vice Chancellor in Zimbabwe, a world renowned academic and diplomat par excellence, you were wise and diligent enough to build a legacy which has outlived you Prof Primrose Kurasha, all by the grace of God. My dear sister, best friend and Economist of note, Flora M.N. Kurasha, your knees keep me standing. Dear reader, enjoy the read! Primrose Egnetor Ruvarashe Kurasha Editor-in-Chief 2019